A history of discoveries and disappearances of the rare annual plant Lythrum thesioides M.Bieb.: new insights into its ecology and biology. Issue 2 (2nd April 2020) - Gazaix, Antoine; Klesczewski, Mario; Bouchet, Michel-Ange; Cartereau, Manuel; Molina, James; Michaud, Henri; Muller, Serge D.; Pirsoul, Lionel; Gauthier, Perrine; Grillas, Patrick; Thompson, John D.
ABSTRACT: Mediterranean temporary pools are threatened ecosystems that host a unique plant community, mostly composed of annual species with large and long-lived seed banks. The longevity of their seed bank, the scarcity of their habitat, the small size of their populations and the low frequency of above-ground vegetation result in a low probability of detection of these species. The discovery of new populations of such rare species are thus important for our understanding of the ecology of the temporary pool ecosystem. Lythrum thesioides M.Bieb., 1808 is a very rare annual species of temporary pools and river banks which was thought to be extinct in the South of France until 1998. Here, we review the distribution of the species and report the recent discovery of a population during a targeted search combining historical data on wetland occurrence on a particular geological substrate. We present new information on its autecology, pollen morphology and the karyotype. Only three populations are currently known worldwide for Lythrum thesioides, and only one of these has favorable management conditions. Thus, we outline new conservation perspectives in the context of a targeted search project and the conservation management of one population.